1996
DOI: 10.1007/bf02349044
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the reduced enamel epithelium just after tooth emergence in rats

Abstract: The reduced enamel epithelium transforms into a stratified squamous epithelium, i.e. a junctional epithelium, as the tooth erupts. In this study, we observed apoptosis in the reduced enamel epithelia of rats just after tooth eruption and before complete junctional epithelium formation, by the TUNEL method and electron microscopy. TUNELpositive reactions were scattered in the reduced ameloblasts and in the external cells of the reduced enamel epithelium. Electron microscopic observation confirmed features of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…4H ). To further confirm the rapid ameloblastic differentiation of hKSCs in chimeric tooth germs, we further performed immunohistochemistry and TUNEL assays to examine the expression profiles of amelogenin and ameloblastin, two molecular markers for differentiating ameloblasts [ 40 , 41 ], and the programmed cell death at various time points [ 42 ]. Strikingly, we found that expression of amelogenin and ameloblastin was not detectable in the hKSC-derived dental epithelia in the recombinants at day 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4H ). To further confirm the rapid ameloblastic differentiation of hKSCs in chimeric tooth germs, we further performed immunohistochemistry and TUNEL assays to examine the expression profiles of amelogenin and ameloblastin, two molecular markers for differentiating ameloblasts [ 40 , 41 ], and the programmed cell death at various time points [ 42 ]. Strikingly, we found that expression of amelogenin and ameloblastin was not detectable in the hKSC-derived dental epithelia in the recombinants at day 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tooth development undergoes various stages, with the formation of tooth crown through the differentiation of dentin-secreting odontoblasts and enamel-producing ameloblasts. Ameloblasts are lost via their transformation and apoptosis upon tooth eruption (Abiko et al, 1996), making it impossible to repair or replace lost/damaged enamel in erupted teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase in the active transport of mineral ions into the matrix during this stage accelerates enamel crystal growth in both width and thickness until the tissue volume is eventually occluded by mineral (6). Finally, the ameloblasts reduce, undergo apoptosis and on tooth eruption, are completely lost (7). …”
Section: Introductionmentioning
confidence: 99%